Hybrid routing in delay tolerant networks - Mayer, Christoph P. (KIT Scientific Publishing, 2012)
This work addresses the integration of today's infrastructure-based networks with infrastructure-less networks. The resulting Hybrid Routing System allows for communication over both network types and can help to overcome cost, communication, and overload problems. Mobility aspect resulting from infrastructure-less networks are analyzed and analytical models developed. For development and deployment of the Hybrid Routing System an overlay-based framework is presented.